Whole Genome and Transcriptome Sequencing of Two Multi-Drug Resistant Mycobacterium tuberculosis Strains to Facilitate Illustrating Their Virulence in vivo - Tang, Jun; Liu, Zhihao; Shi, Ya'nan; Zhan, Lingjun; Qin, Chuan (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis clinical strains usually possess traits different from the laboratory strains like H37Rv, especially those clinical drug resistant strains. With whole genome and transcriptome sequencing, we depicted the feature of two multi-drug resistant Mtb strains in resistance and virulence. Compared with H37Rv, the differential expressed genes (DEGs) of the MDR strains showed featured enrichment in arginine biosynthesis, fatty acid biosynthesis, and metabolism pathway. In the subset of virulence genes, the overlapping DEGs of the MDR strains exhibited downregulation of the cluster in type VII secretion system. In the mice experiment, the MDR strains showed attenuated but distinct virulence, both in survival rate and pathology. Taken together, the whole genome and transcriptome analysis could help understand the unique feature of the MDR strains both in resistance and virulence.